Analysis of Economic Growth, Minimum Wage, Unemployment, and HDI on Income Distribution Inequality in Sulawesi - Fahrur Rozi, Muhammad; Dwi Atmanti, Hastarini (Lafadz Jaya Publisher, 2024)
This study aims to analyze the influence of economic growth, minimum wage, unemployment, and the Human Development Index on income distribution inequality in 6 provinces in Sulawesi during the period 2013-2023. This study uses quantitative analysis with the panel data regression analysis method using the Random Effect Model (REM). The data for this research is secondary data obtained from the Central Statistics Agency of Indonesia. The research results show that simultaneously, independent variables have a significant effect on the dependent variable. However, partially, economic growth and the minimum wage have a negative and significant effect on income distribution inequality, while unemployment and the human development index do not affect income distribution inequality. The results of the coefficient of determination test show that the independent variables explain 49% of their influence on the income inequality variable, while the remaining 51% is explained outside the variables.